Dearomative Dual Functionalization of Aryl Iodanes. Issue 48 (15th October 2019) - Zhao, Weizhao; Huang, Xin; Zhan, Yaling; Zhang, Qifeng; Li, Dongyang; Zhang, Yage; Kong, Lichun; Peng, Bo
Abstract: Herein we describe the dearomatization of aryl iodanes through an unprecedented "rearrangement/addition" sequence. The process consists of two stages. First, a rapid [3, 3] sigmatropic rearrangement of the aryl iodane with an α‐stannyl nitrile affords a highly electrophilic dearomatized intermediate at −78 °C. A low‐temperature rearrangement then enables the unstable dearomatized species to be trapped in situ with various nucleophiles. As a consequence, the reaction not only breaks the aromaticity of the aryl iodane but also sequentially installs two different functional groups, thus resulting in a polysubstituted alicyclic product. Abstract : Room for two : The success of a novel rearrangement/addition sequence for the dearomatization of aryl iodanes hinges on the rapid rearrangement (−78 °C, 10 min), which allows for the low‐temperature trapping of unstable dearomatized intermediates with an array of nucleophiles (see scheme). The introduction of an α‐stannyl nitrile and then a second nucleophile enabled the synthesis of a wide range of polysubstituted alicyclic compounds.